KAJIAN RANTAI PERSEDIAAN BARANG (SUPPLY CHAIN) AGROINDUSTRI TEMPE DI KABUPATEN JEMBER - Astri Maesyaroh Ningtyas; Yuli Hariyati; Triana Dewi Hapsari (University of Jember, 2018)
This study aimed to learn about, (1) Supply Chain, (2) Economic Order Quantity; Lead time ordering; Reorder point of soybean at an agroindustrial tempe. The results showed that: (1) Supply chain on agroindustrial tempe in Jember showed a different pattern: (a) The Supplier of soybean - agroindustrial tempe - outlets - consumer (agroindustrial tempe “Makmur”, “Rizqy”) (b) The Supplier of soybean - agroindustrial tempe - consumer (agroindustrial tempe “Makmur”, “Sumber Mas”, “Pratama”, “Rizqy”, and “UD.Rahayu”) (2) EOQ (Economic Order Quanttity) on agroindustrial tempe in Jember indicates of non economic result, because the total ordering cost is not equal to the total ordering cost; Lead time on Agroindustry of tempe in Jember is 0,02 day (agroindustrial tempe “Makmur”), 0,25 day (agroindustrial tempe “Sumber Mas”), 0,02 day (agroindustrial tempe “Pratama”), 0,04 day (agroindustrial tempe “Rizqy”), and 0,04 day (agroindustrial tempe “UD. Rahayu”); Reorder point of feedstock (soybean) in agroindustrial tempe in Jember is 1.5 kg (agroindustrial tempe “Makmur”), 250 kg (agroindustrial tempe “Sumber Mas”), 2 kg (agroindustrial tempe “Pratama”), 4 kg (agroindustrial tempe “Rizqy”), and 4 kg (agroindustrial tempe “UD. Rahayu”) Keywords: supply chain, Economic Order Quantity, Lead time ordering, Reorder point, and agroindustrial tempe.